1999
DOI: 10.3758/bf03207725
|View full text |Cite
|
Sign up to set email alerts
|

The bits and bytes of computer/internet addiction: A factor analytic approach

Abstract: A factor analytic approach was used to explore possible constructs underlying so-called computer/Internet addiction. A 94-item survey was developed, from which two major and two minor factors were derived. Factor 1 focused on problematic computer-related behaviors in heavy users of the Internet, whereas Factor 2 focused on the usefulness and general purpose nature of computers and the Internet. Factor 3 isolated a combination of use of the Internet for sexual gratification and shyness/introversion, and Factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
60
0
9

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 11 publications
1
60
0
9
Order By: Relevance
“…Moreover, the geographic and the socioeconomic factors prevent the transfer of rapid information between the patients and the healthcare providers. With the use of the internet, through broadband high capacity network connections, we can cross these barriers to provide timely medical care in every nook and corner of the country [6]. To achieve this, it is important for the In this study, 42% Female and 24% Male students were using computers and the internet to get general information, 80% of the students used computers for thesis or research work, 52% Females and 22% Males used computers for entertainment and 42% of the students used computers for others purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the geographic and the socioeconomic factors prevent the transfer of rapid information between the patients and the healthcare providers. With the use of the internet, through broadband high capacity network connections, we can cross these barriers to provide timely medical care in every nook and corner of the country [6]. To achieve this, it is important for the In this study, 42% Female and 24% Male students were using computers and the internet to get general information, 80% of the students used computers for thesis or research work, 52% Females and 22% Males used computers for entertainment and 42% of the students used computers for others purposes.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to premorbid conditions, another study has suggested that preoccupation with the Internet may be related to various clinical problems that predate Internet use, including depression, anxiety, and low self-esteem (3). There also exists a small body of literature examining the personality traits of addiction-prone individuals, which include increased shyness, introversion, and social withdrawal (8,(9)(10)(11). The results of the literature thus far suggest not only that excessive Internet use can have potential negative effects on a person's functioning but also that certain symptom clusters may predispose some individuals to preoccupation with the Internet.…”
mentioning
confidence: 99%
“…Sex is reported to be the most frequently searched topic on the Internet (Cooper & Burg, 2000;Freeman-Longo & Blanchard, 1998), and cybersex became a new phenomenon, not only for single people but also for married ones (e.g., Young, Griffin-Shelley, Cooper, O'Mara, & Buchanan, 2000). Pratarelli, Browne, and Johnson (1999), for instance, found that 20% of a college sample reported using the Internet for sexual arousal purposes. The growing sexual content of the mass media and Internet has been found to predict sexual behavior patterns (Brown et al, 2006;Collins et al, 2004), leading individuals to adopt more permissive sexual norms and to become sexually active at a younger age (Brown et al, 2006).…”
mentioning
confidence: 99%